The contribution of microglia to early synaptic compensatory responses that precede β-amyloid-induced neuronal death - Sara Merlo (Nature Portfolio, 2018)
Abstract Glial-neuronal cross-talk has a critical role in the development of neurodegenerative conditions, including Alzheimer’s Disease, where it affects neuronal responses to β-amyloid peptide (Aβ)-induced toxicity. We set out to identify factors regulating synaptic responses to Aβ, dissecting the specific role of glial signaling. A low concentration of aggregated Aβ42 induced selective up-regulation of mature brain-derived neurotrophic factor (BDNF) expression and release in rat organotypic hippocampal cultures as well as in cortical pure microglia. Conditioned media from resting (CMC) or Aβ42-treated (CMA) microglia were tested for their effects on synaptophysin expression in SH-SY5Y neuronal-like cells during challenge with Aβ42. Both CMC and CMA prevented Aβ-induced synaptophysin loss. In the presence of Aβ + CMA, synaptophysin was over-expressed, although it appeared partly clumped in cell bodies. Synaptophysin over-expression was not directly dependent on BDNF signaling on neuronal-like cells, but relied on autocrine BDNF action on microglia. FM1-43 labeling experiments revealed compromised synaptic vesicle recycling in Aβ42-treated neuronal-like cells, rescued by microglial conditioned medium. In these conditions, significant and prolonged neuroprotection was observed. Our results point to microglia as a target for early intervention, given its positive role in supporting neuronal compensatory responses to Aβ synaptotoxicity, which potentially lead to their extended survival.